Inorganic structural chemistry - Muller, Ulrich (John Wiley & Son, 2007)
This book describes the structural principles of inorganic molecular and solids using traditional concept as well as modern approaches. It includes the systematic ordering of the recognized structure types, relationships amongst them and the link between structure and properties